STRATEGI FUNDRAISING DANA WAKAF PADA BADAN WAKAF AL-QUR’AN (BWA) CABANG MEDAN - Iswari Indah (Jurnal El Rayyan: Jurnal Perbankan Syariah, 2022)
Objective in the research is how to implement strategy fundraising fund waqf which is conducted in Badan Wakaf Al-Qur’an (BWA) Cabang Medan, what are the barriers to implementation strategy fundraising fund waqf in Badan Wakaf Al-Qur’an (BWA) Cabang Medan. This research aims to determine strategy fundraising fund waqf in Badan Wakaf Al-Qur’an (BWA) Cabang Medan, to know the barriers to implementation strategy fundraising fund waqf in Badan Wakaf Al-Qur’an (BWA) Cabang Medan. This research was conducted by collecting data namely : Interview, Observation and Documentation. Research subjects in Badan Wakaf Al-Qur’an (BWA) Cabang Medan. The research result obtained are strategy fundraising used in Badan Wakaf Al-Qur’an (BWA) Cabang Medan in the form of presentation, booth, waqf pick-up, charity box, online donation, waqf goes school and action executive. Barriers to implementation strategy fundraising fund waqf in Badan Wakaf Al-Qur’an (BWA) Cabang Medan in the form of lack of human resources (fundraiser) in the implementation of fundraising, did not get location permit, remote fundraising location, lack of public knowledge about waqf and bad view from public